PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY PT. INDONESIA POWER UPJP KAMOJANG - Cita Insaniah Muhammad; Santoso Tri Raharjo; Risna Resnawaty (Universitas Padjadjaran, 2018)
ABSTRACT The concept of corporate social responsibility has been around for thousands of years. The concept of corporate social responsibility has increasingly developed at the beginning of the industrial revolution which began to focus on the problem of corporate responsibility. The implementation of CSR is considered as an effort to create good companies in the public eye. John Elkinkon through the concept of